Protocol for evaluation of suitability of the copper twisted-pair access network for the IPTV service (2012)
With the development of different broadband technologies in access, there is the greatest technological breakthrough that allows providing various services through it (convergence). Appear and telecom operators currently providing voice and data services by the traditional copper pair, and wishing to provide services such as IPTV, but have limited ability to transfer data in access. This technical limitation requires assessing the access network as a prerequisite and essential for the provision of a service through a process, a verification of the parameters versus standards and / or vendor specifications and measurement technology, for this reason it has decided address this important issue in this work. For the operator from a technical perspective, marketing and service support is of utmost importance to have the assurance that the service will be deployed and supported within the operating parameters suggested by the standards and providers.